Penerapan Maqashid Al-Shari‘ah Pada Lembaga Keuangan Islam - Achmad Fageh (JES (Jurnal Ekonomi Syariah), 2018)
Islamic finance made its first appearance in the 1970s. Since its inception, Islamic finance has made phenomenal progress and progressed beyond its traditional market into a global phenomenon. The recent global financial crisis has also brought Islamic finance into navel attention. Regardless of the minimal impact accused on Islamic finance, the crisis offers an opportunity for introspection and evaluation. It is inevitable to determine whether it can be a viable alternative to conventional systems in global financial markets. Therefore, Islamic financial institutions must ensure that all transactions are in accordance with sharia, not only in the form and technical law, but more importantly, in their economic substance, which should be based on the objectives outlined by the sharia, also known as maqa>s}id al-shari>’ah. This article aims at examining the concept of maqa>s}id al-shari>’ah  of Islamic jurisprudence in order to appreciate its contribution toward more comprehensive, rational and realistic answers to contemporary financial issues and thereby to increase the awareness of the maqasid approach in structuring and developing Islamic finance products. For this purpose, the author examine the literal and conceptual meaning of maqa>s}id al-shari>’ah  and scrutinise its position in Islamic law. They also highlight the essential elements of maqasid al-shari'ah and explain how this approach may contribute to better solutions for various Islamic finance issues and challenge. Islamic finance as an institution based on the ethical and moral framework of Islamic law assumes a distinctive role in society. Furthermore, the maqashid al-shari’ah framework also implies that. The characteristics of Islamic finance institutions are shaped by higher Islamic legal objectives that emphasize overall social and economic goodness rather than infectious greed and infectious individualism. Productive benefits are commendable as long as they are in accordance with the principles of justice as determined in the sharia. Keywords: Framework, Maqashid al-Shari‘ah, Islamic Finance